2009
DOI: 10.1097/01.aids.0000363782.50580.d8
|View full text |Cite
|
Sign up to set email alerts
|

The use of routine monitoring and evaluation systems to assess a referral model of family planning and HIV service integration in Nigeria

Abstract: Family planning-HIV integration using the referral model improved family planning service utilization by clients accessing HIV services, but further improvement is possible. Male utilization of family planning services also improved. The government of Nigeria should review the family planning user fee policy and scale up the integration in primary healthcare facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…ART/PMTCT services may also provide an opportunity to strengthen family planning services and improve access to hormonal contraceptives and reproductive health services for women who wish to limit their fertility [32]. The associations between availability and use of PMTCT with integrated family planning services and hormonal contraceptive use are unclear, but availability of these services has increased contraceptive use among women in some sub-Saharan African settings [33-35]. Strengthening of family planning services during ART/PMTCT may have implications for reducing unintended pregnancies and decreasing MTCT, and may lessen the trend of increasing fertility desires of women with improved availability of PMTCT services with ART.…”
Section: Discussionmentioning
confidence: 99%
“…ART/PMTCT services may also provide an opportunity to strengthen family planning services and improve access to hormonal contraceptives and reproductive health services for women who wish to limit their fertility [32]. The associations between availability and use of PMTCT with integrated family planning services and hormonal contraceptive use are unclear, but availability of these services has increased contraceptive use among women in some sub-Saharan African settings [33-35]. Strengthening of family planning services during ART/PMTCT may have implications for reducing unintended pregnancies and decreasing MTCT, and may lessen the trend of increasing fertility desires of women with improved availability of PMTCT services with ART.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] There is a growing body of literature that describes the effect of integrated FP/HIV services introduced through pilot studies or as components of clinical trials, but routine measurement of regular programme implementation is essential. [4][5][6][7] However, efforts to record routine services have been hampered by the lack of standardised indicators that Key message points ▸ In most cases it is feasible to collect data on the proportion of HIV clients receiving family planning (FP) services/ referral, and FP clients receiving an HIV test/referral. ▸ Services need to develop a better understanding of their daily and active client loads to assist programme managers in allocating resources effectively and efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…Authors of several research studies in Africa found that the health facility plays an important role in client contraceptive adoption and continuation (Bradley, Gillespie, Kidanu, Bonnenfant, & Karklins, 2009; Chabikuli, et al, 2009; Liambila, et al, 2009; Ngure, et al, 2009; Spaulding, et al, 2009). In South Africa, the contraceptive method mix may play an important role in contraceptive continuation.…”
Section: Introductionmentioning
confidence: 99%
“…We explored factors previously identified in the literature as important to contraceptive use and continuation, to determine whether these were also important to clients and providers in this setting. These factors included: client waiting times, amount of time providers spend with clients, client provider interactions when discussing contraception, discussion of contraceptive side effects, whether or not a client’s HIV status played a role in the contraceptive methods promoted to them, discussion of condoms, patient’s satisfaction with the family planning services, and patient and provider’s suggestions about how to improve family planning services (Bradley, et al, 2009; Chabikuli, et al, 2009; Liambila, et al, 2009; Ngure, et al, 2009; Spaulding, et al, 2009). Authors of previous studies in South Africa and other sub-Saharan African countries examined family planning service provision from either the client or the nurse perspective.…”
Section: Introductionmentioning
confidence: 99%